ANALISIS POLA ASUH DALAM NOVEL 7 PRAJURIT BAPAK KARYA WULAN NUR AMALIA DAN PEMANFAATANNYA SEBAGAI BAHAN AJAR PEMBELAJARAN ANALISIS NOVEL DI SMA - Nur Fitri Robiah; Khoirul Fajri; Muhammad Sholeh (Jurnal PENEROKA, 2026)
This study aims to describe the parenting patterns present in the novel *7 Prajurit Bapak* by Wulan Nuramalia and their utilization as teaching material in the preparation of a novel analysis learning module at the high school level. The analysis is focused on narratives and dialogues that contain elements of parental parenting toward children, to reveal the moral, social, and psychological values contained in the story. This study uses a descriptive qualitative method, with data sources in the form of excerpts from the novel *7 Prajurit Bapak*. The research data is supported by relevant theories from books and scholarly articles. The data is analyzed through a careful grouping process, then presented in the form of tables to facilitate the analysis and discussion process. The research results show that the parenting style of the parents in the novel tends to be authoritative; however, in certain situations, the character of the Father also applies authoritarian, permissive, and neglectful styles. This combination of parenting styles shapes a child character that is responsible, independent, socially minded, solidaristic, and highly empathetic toward others. This research is not only an analysis of literary elements in the novel but also relates to studying parenting theory in child developmental psychology, thereby simultaneously providing multidisciplinary learning, namely literary studies and character education. These findings can be utilized to train students' critical thinking skills through discussions on the analysis of intrinsic elements and the impact of parenting styles on child character development. The teaching module created based on this analysis has been validated by three experts and declared suitable for use with some minor revisions.